2009
DOI: 10.2337/db09-0214
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Human Skeletal Muscle Reveals Novel Abnormalities in Obesity and Type 2 Diabetes

Abstract: OBJECTIVEInsulin resistance in skeletal muscle is an early phenomenon in the pathogenesis of type 2 diabetes. Studies of insulin resistance usually are highly focused. However, approaches that give a more global picture of abnormalities in insulin resistance are useful in pointing out new directions for research. In previous studies, gene expression analyses show a coordinated pattern of reduction in nuclear-encoded mitochondrial gene expression in insulin resistance. However, changes in mRNA levels may not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
243
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(259 citation statements)
references
References 50 publications
16
243
0
Order By: Relevance
“…Moreover, significant positive correlations were also observed for summative spot volumes (sum of volumes of all spots with the same identified protein) relating to cytoplasmic malate dehydrogenase (MDH1), an enzyme controlling TCA cycle pool size and providing contractile function [27], and the mitochondrial enzymes ACO2, ATP5A1, ATP5B and GBAS. These results, suggesting reduced TCA cycle and mitochondrial protein content in insulin resistance, are consistent with previous findings of reduced enzyme activities [10,28,29], protein expression [16,17,30], altered phosphorylation [16,31,32], altered transcript levels [10,33,34] or altered flux through mitochondrial ATP synthase [8].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, significant positive correlations were also observed for summative spot volumes (sum of volumes of all spots with the same identified protein) relating to cytoplasmic malate dehydrogenase (MDH1), an enzyme controlling TCA cycle pool size and providing contractile function [27], and the mitochondrial enzymes ACO2, ATP5A1, ATP5B and GBAS. These results, suggesting reduced TCA cycle and mitochondrial protein content in insulin resistance, are consistent with previous findings of reduced enzyme activities [10,28,29], protein expression [16,17,30], altered phosphorylation [16,31,32], altered transcript levels [10,33,34] or altered flux through mitochondrial ATP synthase [8].…”
Section: Discussionsupporting
confidence: 81%
“…Thus, these two-dimensional-gel proteomic studies delivered largely consistent findings. Another recent study used one-dimensional SDS-PAGE and label-free MS/MS-based identification and quantification [17]. Of 92 proteins increased more than twofold and of these, the 15 significantly different between OB and/or obese type 2 diabetic and LE participants in that study, only six and one, respectively, were also identified by us.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Proteomic methods have been used to investigate human and mouse obesity, but most reports have focused on changes in adipose tissue. [3][4][5][6] Recent results suggest that the blood-brain barrier (BBB) is activated in obesity; for example, mice with adult-onset obesity show resistance to leptin transport across the BBB, region-specific astrogliosis, and upregulation of astrocytic leptin receptors. 7,8 The BBB is a regulatory interface between the central nervous system (CNS) and the peripheral circulation.…”
Section: Introductionmentioning
confidence: 99%